Airmed-cardio a GSM and Internet services-based system for out-of-hospital follow-up of cardiac patients. - Salvador, C.H.
A platform built around three information entities (patient, health-care_agent, and central_station) was designed to enable patients with chronic heart disease (in stable condition; emergency situations were excluded deliberately) to complete specifically defined protocols for out-of-hospital follow-up and monitoring. The patients belonged to one of four specific risk groups: arterial hypertension, malignant arrhythmias, heart failure, and postinfarction rehabilitation. They were provided with portable recording equipment and a cellular phone that supported data transmission [electrocardiogram (ECG)] and wireless application protocol (WAP) (remaining parameters and ad hoc questionnaires). The central station was an automatized platform, with no human operator. The information received was organized chronologically in patient folders. The health-care_agents had continuous and secure access to the patient folders, through tools based on the world wide web and WAP, and to short messages sent by their patients. A pilot project was conducted with 89 patients (mean length of participation: 50.1 days). A total of 2168 ECGs (mean duration transmission=2 min/30 s; network errors < 0.1%) and 4011 short messages (none lost, in 95% of cases 30 s<1 min) were transmitted; 6083 WAP sessions (mean duration=3 min 11 s; network failures < 0.1%) were held. The functionality of the platform was also evaluated, analyzing the subjective component of usability, showing the evolution of patient acceptance over time.
Keywords: ECG; GSM; Internet services-based system; Ad hoc questionnaires; Arterial hypertension; Cardiac patients; Cellular phone; Chronic heart disease; Data transmission; Electrocardiogram; Global system for mobile communication; Health-care agents; Heart failure; Information entities; Malignant arrhythmias; Network errors; Out-of-hospital follow-up.; Portable recording equipment; Postinfarction rehabilitation; Secure access; Short message service; Telecardiology; Wireless application protocol; World wide web